Citizen Activation in Contemporary Collective Housing. Barcelona Experiences - Turrado, Isabel Aparici (Docomomo Journal, 2014)
This paper explores contemporary collective housing as a community resource and living heritage. The first part of the article is a conceptualization of citizen activation as a valid concept to merge actions that can transform housing into a platform to promote social cohesion. The second part lists the steps to reach citizen activation. The article highlights some examples in Barcelona: buildings where some activation activities have been stimulated and others that could start the process.